Does attraction to frugivores or defense against pathogens shape fruit pulp composition? - Cazetta, Eliana [UNESP]; Schaefer, H. Martin; Galetti, Mauro [UNESP] (Springer, 2008)
Fruit traits evolve in response to an evolutionary triad between plants, seed dispersers, and antagonists that consume fruits but do not disperse seeds. The defense trade-off hypothesis predicts that the composition of nutrients and of secondary compounds in fruit pulp is shaped by a trade-off between defense against antagonists and attraction to seed dispersers. The removal rate model of this hypothesis predicts a negative relationship between nutrients and secondary compounds, whereas the toxin-titration model predicts a positive relationship. To test these alternative models, we evaluated whether the contents of nutrients and secondary compounds can be used to predict fruit removal by mutualists and pathogens in 14 bird-dispersed plants on a subtropical island in São Paulo state, southeastern Brazil. We selected eight to ten individuals of each species and prevented fruit removal by covering four branches with a net and left fruits on four other branches available to both, vertebrate fruit consumers and pathogens. The persistence of ripe fruits was drastically different among species for bagged and open fruits, and all fruit species persisted longer when protected against seed dispersers. We found that those fruits that are quickly removed by vertebrates are nutrient-rich, but although the attack rate of pathogens is also high, these fruits have low contents of quantitative defenses such as tannins and phenols. Thus, we suggest that the fruit removal rate by seed dispersers is the primary factor selecting the levels of fruit defense. Likewise, nutrient-poor fruits have low removal of seed dispersers and low probability of attack by pathogens. These species retain ripe fruits in an intact condition for a prolonged period because they are highly defended by secondary compounds, which reduce overall attractiveness. However, this strategy might be advantageous for plants that depend on rare or unreliable dispersers.
Keywords: fruit pathogens; fruit removal; secondary compounds; plant-animal interactions